2020
DOI: 10.1007/s12325-020-01590-w
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Chart Review Study of Real-World Use of Talimogene Laherparepvec in Unresectable Stage IIIB–IVM1a Melanoma in Four European Countries

Abstract: Introduction Talimogene laherparepvec (T-VEC; IMLYGIC ® , Amgen Inc.) is an oncolytic immunotherapy approved in Europe for the treatment of unresectable metastatic melanoma (stage IIIB–IVM1a). This study characterised real-world use of T-VEC in four European countries. Methods Data on demographics, treatment pattern, safety, and clinical effectiveness were examined in a retrospective chart review of patients with stage IIIB–IVM1a unresectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The authors concluded that T-VEC may be an important consideration for older patients with melanoma who may not be able to tolerate other systemic options. Overall, the real-world data suggests that objective responses and safety profile for T-VEC in melanoma patients are comparable to those observed in the OPTiM phase III clinical trials (van Akkooi et al, 2021). Clinical benefit may be especially high in older patients and in those receiving T-VEC as firstline treatment.…”
Section: Real World Experience With T-vecmentioning
confidence: 61%
See 2 more Smart Citations
“…The authors concluded that T-VEC may be an important consideration for older patients with melanoma who may not be able to tolerate other systemic options. Overall, the real-world data suggests that objective responses and safety profile for T-VEC in melanoma patients are comparable to those observed in the OPTiM phase III clinical trials (van Akkooi et al, 2021). Clinical benefit may be especially high in older patients and in those receiving T-VEC as firstline treatment.…”
Section: Real World Experience With T-vecmentioning
confidence: 61%
“…This has been described as an "abscopal" or "anamnestic" response (Andtbacka et al, 2016a). Animal models have confirmed that injection of an index tumor can cause regression of uninjected tumors in an immune-dependent manner (Zamarin et al, 2014). Thus, OVs provide two independent mechanisms that can reinforce tumor-specific immune clearance.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The use of T-VEC in advanced melanoma is also being evaluated in combination therapy approaches, e.g. together with ipilimumab and pembrolizumab (194,195), with the aim of increased efficacy in patients with visceral metastases. Other vaccine therapies, including dendritic cell-based, peptide-based and vector-based vaccines are also in the testing phase and so far, the results have not been assuring (196).…”
Section: Therapeutic Approaches In Melanomamentioning
confidence: 99%
“…In addition to T-VEC, non-neurovirulent rhinovirus:poliovirus chimera (PVSRIPO) has been described for treatment-refractory melanoma in a phase I clinical trial showing promising antitumor activity [66]. However, to date, the majority of data regarding virotherapy and melanoma treatment are limited to T-VEC, likely because this is the only FDA-approved oncolytic virus for the treatment of melanoma [67][68][69][70].…”
Section: Virotherapy and Melanomamentioning
confidence: 99%